An integrative histopathological and epigenetic characterization of primary intracranial mesenchymal tumors, FET:CREB‐fused broadening the spectrum of tumor entities in comparison with their soft tissue counterparts. (27th July 2021) - Tauziède‐Espariat, Arnault; Sievers, Philipp; Larousserie, Frédérique; Benzakoun, Joseph; Guillemot, Delphine; Pierron, Gaëlle; Duchesne, Mathilde; Uro‐Coste, Emmanuelle; Roux, Alexandre; Vasiljevic, Alexandre; Fenouil, Tanguy; Meyronet, David; et al.
Abstract: FET:CREB fusions have been described in a variety of tumors from various phenotypes. Recently, these fusion transcripts were reported in intracranial tumors, variably named intracranial mesenchymal myxoid tumors or angiomatoid fibrous histiocytomas. Controversy remains concerning the terminology for these tumors. Here, we report 11 cases of central nervous system mesenchymal tumors with proven FET:CREB fusion. Most DNA methylation profiles were not classifiable using the Heidelberg Brain Tumor or Sarcoma Classifier (v11b4/v12.2). However, by using unsupervised t‐SNE and hierarchical clustering analyses, six of the cases constituted a distinct cluster. The remaining four tumors showed no obvious relation to any of the other referenced classes but were close to the clusters of extra‐CNS angiomatoid fibrous histiocytomas (n = 1), clear cell sarcomas (n = 1), or solitary fibrous tumors (n = 2). Our findings confirm that intracranial FET:CREB‐fused tumors do not represent a single molecular tumor entity, although most samples clustered close to each other, indicating the existence of a distinct epigenetic group that could potentially be partially masked by the low number of cases included. Further analyses are needed to characterize intracranial FET:CREB fused‐defined tumors in more detail. Abstract : Our series includes 11 cases of central nervous system mesenchymal tumors with proven EWSR1 fusion with clinical, histopathological, genetic and epigenetic analyses. Our findings show that intracranial EWSR1:CREB fused‐defined tumors do not represent a single molecular tumor entity, but instead largely cluster into a new DNA methylation class corresponding to the suggested new terminology of "primary intracranial myxoid sarcoma, with EWSR1‐fusion".